Potential role of ATP‐binding cassette transporters against acaricides in the brown dog tick Rhipicephalus sanguineus sensu lato. Issue 1 (21st December 2014) - CAFARCHIA, C.; PORRETTA, D.; MASTRANTONIO, V.; EPIS, S.; SASSERA, D.; IATTA, R.; IMMEDIATO, D.; RAMOS, R. A. N.; LIA, R. P.; DANTAS‐TORRES, F.; KRAMER, L.; URBANELLI, S.; et al.
Abstract ATP‐binding cassette (ABC) transporters have been shown to be involved in pesticide detoxification in arthropod vectors and are thought to contribute to the development of drug resistance. Little is currently known about the role they play in ticks, which are among the more important vectors of human and animal pathogens. Here, the role of ABC transporters in the transport of fipronil and ivermectin acaricides in the tick Rhipicephalus sanguineus (Ixodida: Ixodidae) was investigated. Larvae were treated with acaricide alone and acaricide in combination with a sub‐lethal dose of the ABC transporter inhibitor cyclosporine A. The LC50 doses and 95% confidence intervals (CIs) estimated by mortality data using probit analysis were 67.930 p.p.m. (95% CI 53.780–90.861) for fipronil and 3741 p.p.m. (95% CI 2857–4647) for ivermectin. The pre‐exposure of larvae to a sub‐lethal dose of cyclosporine A reduced the LC50 dose of fipronil to 4.808 p.p.m. (95% CI 0.715–9.527) and that of ivermectin to 167 p.p.m. (95% CI 15–449), which increased toxicity by about 14‐ and 22‐fold, respectively. The comparison of mortality data for each separate acaricide concentration showed the synergic effect of cyclosporine A to be reduced at higher concentrations of acaricide. These results show for the first time a strong association between ABC transporters and acaricide detoxification in R.sanguineus s.l.